The Effects of Tai Chi (Bafa Wubu) on College Students’ Switch Functions and Tracking Study - Xia, Tong; Yin, Hengchan; Cui, Lei; Shen, Qiqi; Hou, Jinmei; Zhang, Jingyi (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract:Background: Switch function refers to the process of switching back and forth operationally or between psychological stereotypes when performing a complex task, and refers to the need for individuals to flexibly change their responses in an appropriate manner to adapt to new requirements when completing a task, which is specifically embodied in the fact that, when two tasks are competing for the same cognitive resources, the process of controlling the interconversion of these two tasks is one of the important components of executive functioning, which influences the development of individuals’ behavioural activities and social adaptations. behavioural activities and social adaptation development. As the builders and successors of the country, poor switching function will lead to difficulties in attention switching and reduced decision-making ability, and even affect the lifelong development of college students. Research has shown that switch functionsing is plastic throughout an individual’s lifespan, and exploring effective interventions to enhance switch functionsing in college students has become a hot topic of interest for researchers in multiple disciplines. Studies in the field of psychology have shown that mental training such as positive thinking training, attention training, meditation training, and breathing training have positive effects on the improvement of switch functionsing. Studies in the field of exercise psychology have found that different exercise programmes, exercise intervention cycles, exercise intensities and single intervention durations have different benefits on the facilitation of switch function, and the relationship between the type, duration, intensity, frequency and other components of exercise, both individually and interactively, and the relationship between them and the switch function still needs to be studied in depth. However, most of the current studies use laboratory exercises (power cycling, running platform) and comprehensive exercise programmes, which have low ecological validity, are not easy to be popularized and promoted to the college student population, affect the promotion and application of exercise programmes in real-life scenarios, and limit the development of research on the use of exercise to promote the switch function in college students. Tai Chi is a traditional Chinese exercise that combines physical and mental unity, mind and body relaxation, and both intention and health and fitness, and contains components such as body movement, breathing, and meditation. Previous studies have shown that Tai Chi has a positive effect on the switch function of individuals. However, most of the studies on Tai Chi and switch function have examined the effects of Tai Chi on switch function at two points in time, before and after the exercise intervention, but have not yet addressed the tracking of its effects, and most of the current study groups are elderly people, with relatively few studies on Tai Chi for college students. Aim of the study: This study took college students as the research object, designed a 16-week intervention programme based on the elements of "form, qi and intention" of Tai Chi (Bafa Wubu), comprehensively applied the measurement methods and techniques of kinesiology and psychology, and adopted a tracking research design to investigate the effects of 16 weeks of Tai Chi (Bafa Wubu) on the switch function and its post-effects, which was the first time to use the Bafa Wubu in Tai Chi. It provides a theoretical and practical basis for the use of Tai Chi (Bafa Wubu) to promote the development of switch function in college students, provides a basis for the design of a long-term exercise intervention programme to promote the healthy development of switch function in college students, and provides scientific evidence for the establishment of Tai Chi as the preferred means of enhancing switch function to assist a healthy China. Therefore, this study has certain theoretical significance and practical value. RESEARCH METHODS: This study was conducted with 89 college students, and a two-factor mixed experimental design of 3 (group: Tai Chi group, walking group, control group) × 3 (time: pre-intervention, post-intervention, and 2 weeks after cessation of the intervention) was adopted, in which subjects were randomly divided into a Tai Chi group, a walking group, and a control group in accordance with the proportion of gender. The Tai Chi group was given a 16-week, three times a week, 60-minute Tai Chi (Bafa Wubu) exercise intervention; the walking group was given a 16-week, three times a week, 60-minute walking exercise intervention; and the control group was given a normal study life. College students’ switch function was measured using the More-odd shifting task before, after, and 2 weeks after the intervention was stopped. Repeated-measures ANOVA was used to compare the changes and differences in the response time and correct rate of college students’ switch function before, after, and 2 weeks after the cessation of the 16-week exercise intervention. The results of the study: (1) repeated measures ANOVA was used to compare the differences in the response time of the switch function before and after the 16-week Tai Chi (Bafa Wubu) exercise intervention and 2 weeks after the intervention was stopped, and it was found that Tai Chi (Bafa Wubu) could enhance the efficiency of the switch function of college students very significantly, and the effect of the intervention was stable for 2 weeks after the intervention was over, and the effect was better than that of walking, and the intervention of walking had very significant enhancement effects on the efficiency of the switch function of college students, and the intervention effect was stable for 2 weeks after the intervention was over. (2) The repeated measures ANOVA was used to compare the differences in the correct rate of switch function before and after the 16-week Tai Chi (Bafa Wubu) exercise intervention and 2 weeks after the intervention was stopped, and it was found that the Tai Chi (Bafa Wubu) exercise could significantly improve the efficiency of the switch function of college students, and the intervention effect was stable for 2 weeks after the intervention, and better than that of the walking group. It was found that Tai Chi (Bafa Wubu) exercise could significantly improve the switch function performance of college students, and the intervention effect was stable within 2 weeks after the intervention, and it was better than that of the walking group. Conclusion: (1) Tai Chi (Bafa Wubu) intervention for 16 weeks can significantly improve the switch function of college students. (2) Walking for 16 weeks was able to significantly improve the switch function. (3) The effect of Tai Chi (Bafa Wubu) on switch function was stable for 2 weeks after the intervention, and the effect was better than that of walking.